KEBIJAKAN PIDANA DALAM TINDAK PIDANA KORUPSI OLEH KORPORASI - Wasahua, Idris (Lex Jurnalica, 2024)
AbstractThis research aims to examine three aspects of criminal policy in cases of corruption committed by corporations, as regulated in Law No. 31 of 1999, as amended by Law No. 20 of 2001 on the Eradication of Corruption Crimes. These aspects are: First, criminal policy regarding acts of corruption that can be held accountable to corporations. Second, criminal policy concerning the system of corporate criminal liability in corruption cases. Third, criminal policy related to criminal sanctions that may be imposed on corruption offenses committed by corporations. This research uses normative juridical research methods.  This research produces the following conclusions: First, acts of corruption that can be committed and made accountable to corporations include all corruption offenses regulated in Chapter II of the Anti-Corruption Law, where the legal subject of the offense includes the element of "Any person." Second, the corporate criminal liability system in corruption offenses consists of fault-based liability, the Identification Theory, and the Vicarious Liability Theory. Third, the criminal sanctions that may be imposed for corruption offenses committed by corporations are as follows: for corporations, the principal penalty imposed is a fine, with the maximum penalty increased by one-third; for officers, the principal penalties include the death penalty, life imprisonment, fixed-term imprisonment, or fines as specified in each article on corruption offenses, as well as additional penalties as stipulated in Article 18, paragraph (1) of the Anti-Corruption Law.Keywords: criminal policy, criminal acts of corruption, corporations AbstrakPenelitian ini bertujuan untuk meneliti tigas aspek kebijakan pidana dalam tindak pidana korupsi yang dilakukan oleh korporasi dalam Undang-Undang Nomor 31 Tahun 1999 sebagaimana telah diubah dengan Undang-Undang Nomor 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi  (UU PTPK) yakni: Pertama, kebijakan pidana terkait tindak pidana korupsi  yang dapat dipertanggungjawabkan terhadap korporasi. Kedua, kebijakan pidana terkait sistem pertanggungjawaban pidana korporasi  dalam tindak pidana korupsi. Ketiga, kebijakan pidana terkait sanksi pidana  yang dapat dijatuhkan terhadap  tindak pidana korupsi yang dilakukan oleh korporasi. Penelitian ini menggunakan metode penelitian yuridis normatif.  Penelitian ini menghasilkan beberapa kesimpulan berikut:  Pertama, tindak pidana korupsi yang dapat   dipertanggungjawabkan terhadap  korporasi adalah semua tindak pidana korupsi yang diatur dalam Bab II UU PTPK yang subyek hukum pelaku tindak pidananya memuat unsur “Setiap orang”.  Kedua, Sistem pertanggungjawaban pidana korporasi dalam  tindak pidana korupsi  terdiri dari  pertanggungjawaban pidana berdasarkan pada  kesalahan (liability based on fault),   teori  Identification,  dan teori Vicarious Liability,   Ketiga, sanksi pidana yang dapat dijatuhkan terhadap  tindak pidana korupsi yang dilakukan oleh korporasi adalah terhadap korporasi dijatuhi pidana pokok berupa denda dengan ketentuan maksimum pidana ditambah 1/3 (satu pertiga), dan terhadap pengurus dijatuhi pidana pokok, baik pidana mati, pidana penjara seumur hidup, pidana penjara untuk waktu tertentu, pidana denda, yang  ketentuan tentang penjatuhannya sebagaimana disebutkan dalam setiap pasal pidana korupsi, serta  pidana tambahan yang disebutkan dalam Pasal 18 ayat (1) UU PTPK.Kata kunci : kebijakan pidana, tindak pidana korupsi, korporasi